Ceria-Promoted and stabilized copper and iron oxides cooperatively catalyze NO efficient degradation by CO. (15th May 2023) - Shi, Xiaobing; Tao, Lin; Tong, Zhangfa; Fan, Minguang; Dong, Lihui; Li, Bin
Highlights: In situ techniques reveal reaction mechanism under reaction conditions. CeO2 stabilizes Cu active species at low temperature by keeping the cyclic transition of Cu 2+ and Cu + . CeO2 stabilizes Fe active species at high temperature by promoting the cyclic transition between Fe 3+ and Fe 2+ . Ceria-Promoted and realized copper and iron oxides cooperatively catalyze NOx efficient elimination. Abstract: The copper and iron oxides highly dispersed on CeO2 composite system was successfully synthesized by solid-state based methods for NO reduction by CO with a certain sulfur and water resistance. The conversion of NO at 100, 150 and 220 °C can reach ∼40 %, ∼80 % and ∼100 % respectively, at space velocity = 65, 000 mL·g −1 ·h −1 . Here, some ex/in-situ characterization techniques are used to explore the active species and catalytic mechanism in the reaction process. The results show that the catalyst system has a large number of defects and contains highly reactive oxygen species. During the reaction, the dominant Ce species can promote the formation of Cu + active species and enhance its relative stability. Also, under higher temperature reaction atmosphere, Ce species can stabilize Fe 3+ and maintain the catalytic performance. The stabilization effect of Ce species on copper and iron makes the catalyst have a quite wider active window. To understand the selective catalytic reduction process of NO by CO, a possible reaction mechanism was proposed by in-situ DRIFTS. Overall, this work provides a possible foundation for understanding the structure, catalytic stability, and activity.